Whispers in the reading room - Gray, Shelley Shepard (Grand Rapids, Michigan : Zondervan, 2015)
"Just months after the closure of the Chicago World's Fair, librarian Lydia Bancroft finds herself fascinated by a mysterious dark-haired and dark-eyed patron. He has never given her his name; he actually never speaks to a single person. All she knows about him is that he loves books as much as she does ... Lydia and Sebastian form a fragile friendship, but when she discovers that Mr. Marks isn't merely a very wealthy gentleman, but also the proprietor of an infamous saloon and gambling club, she is shocked"--Page 4 of cover.
Includes discussion questions.
Includes excerpt from: The loyal heart / Robin Lee Hatcher (pages 341-344).
Keywords: Librarians -- Fiction; Man-woman relationships -- Fiction; Murder -- Fiction; Chicago (Ill.) -- Fiction; Detective and mystery fiction; Religious fiction; Historical fiction